The Influence of IoT (Internet of Things) Based Kinetic Sand Media on the Beginning Writing Skills of 4–5 Year-old Children at Annur Bastari Islamic Kindergarten, Pekanbaru - Purba, Sahkina; Kurnia, Rita; Tambunan, Novidawaty (Journal of English Language and Education, 2025)
The childhood phase is a critical stage for early literacy development, particularly in fostering beginning writing skills. This study aims to determine the effect of Internet of Things (IoT)-based kinetic sand media on the early writing skills of children aged 4–5 years at Annur Bastari Pekanbaru Islamic Kindergarten. The media used is a transparent container filled with kinetic sand, equipped with a pressure sensor and a small speaker. When a child writes letters in the sand, the sensor responds to hand movements and provides automatic feedback in the form of lights and sounds corresponding to the letters touched, creating an engaging and enjoyable learning environment. A quantitative approach with an experimental method was employed using a One Group Pretest-Posttest Design, in which one group of 21 children in Group A received a pretest, treatment, and posttest. Data were analyzed using a t-test and normalized gain to measure the effectiveness of the media in improving early writing skills. The results showed a significant improvement, with the average achievement increasing from 33.13% in the pretest to 81.56% in the posttest. The t-test results indicated a significance value of 0.000 0.05 and a t-count of 18.166 t-table value of 2.086, confirming a significant influence. Prior to treatment, most children were in the Early Developing and Not Yet Developing categories. After using the IoT-based kinetic sand media, their skills improved drastically, with most reaching the Very Well Developing and Developing as Expected categories. This media effectively stimulates early writing skills in a fun and interactive manner, aligning with the technological advancements in early childhood education.